A case report of coexistence of invasive ductal carcinoma and malignant phyllodes tumor in a single breast mass - Mahsa Akbari Oryani; Zahra Nikfarjam (Mashhad University of Medical Sciences, 2022)
Introduction: Coexistence of malignant phyllodes tumor and invasive ductal carcinoma in a breast lesion is a very rare medical condition. In this study, a case of coexistence of invasive ductal carcinoma and malignant phyllodes tumor in a single breast mass was reported. Case presentation: The patient was a 39-year-old woman with a mass in left breast. On the requested ultrasound, the image of a heterogeneous hypovaco mass with an irregular margin with size of 30 × 17 × 24 mm was seen. The patient was candidate for complete removal of the breast and axillary lymph nodes. In the histologic evaluation, an invasive ductal carcinoma with malignant phyllodes component was diagnosed which was confirmed by immunohistochemistry. In immunohistochemical study, ER, PR, HER2 were negative in carcinomatous component and CK was negative in phyllodes stromal component, also KI67 index was 35%. In the evaluation of axillary lymph nodes, one out of 7 lymph nodes involved by invasive ductal carcinoma. The patient was referred for adjuvant chemotherapy using four cycles of doxorubicin, cyclophosphamide every two weeks, and four cycles of paclitaxel every two weeks and then adjuvant radiotherapy. In 20 month follow-up, she was alive with no evidence of disease recurrence. Conclusion: Although coexistence of malignant phyllodes and invasive ductal carcinoma of the breast is very rare, but in breast carcinoma with abnormal microscopic findings, due to the diagnostic and therapeutic importance, the concurrent presence of other breast neoplasms such as phyllodes tumor should be considered. Keywords: